Potential environmental implications of nanoscale zero-valent iron particles for environmental remediation - Min-Hee Jang (Environmental Health and Toxicology, 2014)
Objectives Nanoscale zero-valent iron (nZVI) particles are widely used in the field of various environmental contaminant remediation. Although the potential benefits of nZVI are considerable, there is a distinct need to identify any potential risks after environmental exposure. In this respect, we review recent studies on the environmental applications and implications of nZVI, highlighting research gaps and suggesting future research directions. Methods Environmental application of nZVI is briefly summarized, focusing on its unique properties. Ecotoxicity of nZVI is reviewed according to type of organism, including bacteria, terrestrial organisms, and aquatic organisms. The environmental fate and transport of nZVI are also summarized with regards to exposure scenarios. Finally, the current limitations of risk determination are thoroughly provided. Results The ecotoxicity of nZVI depends on the composition, concentration, size and surface properties of the nanoparticles and the experimental method used, including the species investigated. In addition, the environmental fate and transport of nZVI appear to be complex and depend on the exposure duration and the exposure conditions. To date, field-scale data are limited and only short-term studies using simple exposure methods have been conducted. Conclusions In this regard, the primary focus of future study should be on 1) the development of an appropriate and valid testing method of the environmental fate and ecotoxicity of reactive nanoparticles used in environmental applications and 2) assessing their potential environmental risks using in situ field scale applications.